Substance dependency and treatment issues in South Africa : voices of relapsed involuntary service users - Mkhize, Nkanyiso Nkazimulo; Gutura, Priscilla (Penerbit Universiti Kebangsaan Malaysia, 2021)
South Africa like many countries across the globe is faced with a high prevalence of substance dependence among the youth. Drug treatment is a widely and generally accepted approach to curb substance dependence. Among users who are considered for treatment, the majority are treated on an involuntary basis, however, they relapse. This paper discusses the causes of relapse among in-patient and out-patient involuntary youth service users. The findings emanate from a qualitative study that was conducted in Uthungulu district, in KwaZulu Natal, South Africa. Findings revealed lack of personal motivation for behaviour change, stigmatisation and lack of reintegration of users, lack of aftercare programmes, socioeconomic conditions, poor social support, dual addiction implications and psychological factors as causes of relapse. The paper concludes that lack of effective aftercare programmes opened gaps through which socio-economic challenges and poor social support enabled post-treatment relapse. It is recommended that the social development sector must develop guidelines and treatment programmes designed for the treatment of involuntary service users in both in-patient and out-patient settings.